Ecology and development - Bandhu, Desh(ed.); Bhardwaj, Veena (ed.) (Delhi, 1979)
(Proceedings of the Seminar on Ecology and Development held at the Indian National Science Academy, New Delhi, during September 23-26, 1978)
Keywords: Human Ecology